2019
DOI: 10.3390/su11174699
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Students’ Motivation to Seek Higher Education—A Case Study at a State University in the Czech Republic

Abstract: The quality of universities in the present era is the subject of ever more discussion in the Czech Republic and the EU. Quality is determined both quantitatively and qualitatively, and ever more importance is placed on ratings by students and graduates. The objective of this article is to identify and evaluate factors influencing the motivation of students to seek higher education and their expectations regarding the quality of a university. The data was obtained using questionnaire-based investigation among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…More recent literature indicates that pecuniary reasons are the motivation for students' enrollment into higher institutions. Some of these motivations are implied in their advancement and development of their careers (see Ang et al, 2019;Fajčíková & Urbancová, 2019), while others are clear that big "salaries" are their core motivation (see Arceňo, 2018;Serin, 2018). Also, recent studies assessed the motivation of students outside of the mainstream of the society.…”
Section: Motivation To Acquire Higher Degree In Education: a Methodological Reviewmentioning
confidence: 99%
“…More recent literature indicates that pecuniary reasons are the motivation for students' enrollment into higher institutions. Some of these motivations are implied in their advancement and development of their careers (see Ang et al, 2019;Fajčíková & Urbancová, 2019), while others are clear that big "salaries" are their core motivation (see Arceňo, 2018;Serin, 2018). Also, recent studies assessed the motivation of students outside of the mainstream of the society.…”
Section: Motivation To Acquire Higher Degree In Education: a Methodological Reviewmentioning
confidence: 99%
“…Recent literature indicated that students' motivation has not been accorded necessary attention though it is seen as a catalyst for students' accomplishment and retention (Edgar et al, 2019). Fajčíková and Urbancová (2019) confirmed that future economic stability is one of the factors that contributes to students' quest for higher education. This indirectly indicates that highly-rated job and reasonable salary seem to be an influencer for students' pursuit of higher education (Huang & Ho, 2017).…”
Section: *Corresponding Authormentioning
confidence: 96%
“…(2019) used SEM on the following important factors affecting the choice of HE institutes in India: location, public image, employability, college promotion, fee structure and program quality. With the application of the varimax method and Kaiser-Guttman rule in the factor analysis approach in research by Fajčíková and Urbancová (2018), the following four significant factors that motivated Czech Republic students in their choice of university for higher studies were identified as quality personnel providing instruction, building social status, development of competencies and quality of education process about employment. From a list of 21 choice factors and using segmentation analysis on a quantitative survey (Lee et al ., 2019), the top five critical factors identified for HE in Vietnam were: future job prospects, teaching quality, staff expertise, course content and industry-connect.…”
Section: Literature Reviewmentioning
confidence: 99%